Teachers' strategies for enhancing shy children's engagement in oral activities: necessary, but insufficient?. Issue 7 (7th June 2022) - Nyborg, Geir; Mjelve, Liv Heidi; Edwards, Anne; Crozier, W. R.
ABSTRACT: Shy children can present challenges for teachers aiming at inclusive classrooms. Their educational attainments can be lower than their peers, they may have difficulties in adjustment to school and they can be at risk of meeting clinical criteria for social anxiety disorder. One recurrent finding is that they are often quiet across a range of school situations. The study reported here focused on teachers' strategies to engage shy students in frequently occurring oral activities, such as group work, in elementary school classrooms. Data were gathered through post-observation stimulated-recall interviews with eight teachers who had experience of success with shy students and three focus groups with 11 similarly experienced teachers. The analysis examined teachers' actions with these children to enhance their visible engagement in activities that require oral participation. The findings suggest that although teachers attended to the psychosocial aspects of student engagement, there was little emphasis on the pedagogic purposes of oral activities with these children. We conclude that more attention should be paid to the academic aspects of oral activities when aiming at inclusion for shy children.